Screening Of UGT1A1 Gene And Genotype-Phenotype Correlationship In Neonatal Jaundice From A Sample Of Newborns In Kelantan - Ma'amor, Nur Hasnah (2012)
The rate limiting step of bilirubin excretion is the glucuronidation of bilirubin in the liver, a process that is catalyzed by an enzyme, Uridine glucuronyl transferase. This enzyme is encoded by the UGT1A1 gene. In several populations, mutations in this gene have been shown to cause neonatal jaundice. However data on the Malaysian Malay population are scanty at best. The objectives of this study included: to determine the frequency of variants in the exons of the UGT1A1 gene in a population of term Malay neonates with jaundice and without jaundice, and to correlate the genotype finding with some phenotypic data.